A Contribution To Studies Of Piles Under Dynamic Loads - Synopsis - R. J. Folic (Deep Foundations Institute, 2010)
Investigations of the vibrations of a pile in soil are performed on a dynamic model in the form of a prismatic bar of finite axial and flexural stifnesses with a discrete mass at its free end representing the cap. The soil is represented by a system of springs of constant and variable stiffnesses. Oscillation differential equations are derived by means of the Hamiltonian principle for non-conservative systems. The problem is reduced to a coupled system of two non-linear partial differential equations with corresponding initial-boundary conditions. Frequency equations of longitudinal and lateral linearized equations are formed. The paper determines natural frequencies and oscillation modes. It separately examines longitudinal vibrations excitated by a hermonic force acting upon the pile cap, and lateral vibrations excitated by an impulse acting upon the cap. The results of the numerical processing are presented in respective diagrams in dimensionless form.